Rural growth linkages, poverty, and income distribution - Balisacan, Arsenio M. (The Philippine Review of Business and Economics, 1992)
The paper provides a survey of selected topics and issues in the economics of rural development, namely: concepts and empirical regularities concerning rural growth linkages, poverty, and income distribution; determinants of income source diversification; and demand and supply factors constraining rural growth linkages in the Philippines. The survey draws implications for public policy and further research on the economics of agriculture and rural development.